Bilateral retinal artery occlusion as the initial presentation of infectious endocarditis: a case report - Ana Bárbara Dias Lopes Urzedo; Bruna Predabon; Márcio Adriano Filho; Germano Ramos Boff; Kenzo Hokazono (Journal of Medical Case Reports)
Abstract Background Retinal artery occlusion due to infective endocarditis is rare, and only a few cases have been reported in literature. Systematic and comprehensive studies of patients with this ophthalmological disease may help uncover serious underlying medical conditions. Case presentation We present a case of an 80-year-old Brazilian woman with bilateral retinal artery occlusion as the initial presentation of Erysipelothrix rhusiopathiae endocarditis. Conclusion Infective endocarditis has many different forms of presentation and a high clinical suspicion is often required to reach a diagnosis. This case report highlights the importance of remembering retinal artery occlusion as a complication of infective endocarditis even if concurrent cardiovascular risk factors are present.